(untitled) (Modern education and development, 2024)
This article explores the intersection between language and culture through the lens of sports terminology. Sports vocabulary is not only essential for communication within the realm of athletics but also reflects societal values, cultural identity, and historical contexts. This study examines how sports terms and expressions, such as "home-field advantage" or "team spirit," embody deeper cultural meanings related to competition, unity, and national pride. By analyzing the linguistic implications of sports lexemes, this research highlights how language shapes and is shaped by cultural practices, societal norms, and dynamics in sports.